2015
DOI: 10.1017/s0950268815001272
|View full text |Cite
|
Sign up to set email alerts
|

The impact of heptavalent pneumococcal conjugate vaccine on the incidence of childhood community-acquired pneumonia and bacteriologically confirmed pneumococcal pneumonia in Japan

Abstract: Heptavalent pneumococcal conjugate vaccine (PCV7) was introduced to Japan in 2010. We investigated the impact of PCV7 on childhood community-acquired pneumonia (CAP) and pneumococcal pneumonia (PP). Children aged <5 years living in Chiba city, Japan, who were admitted to hospitals were enrolled to estimate the incidence of CAP based on the mid-year population. PP was determined by the presence of Streptococcus pneumoniae in cultured blood and/or sputum samples of CAP patients. The incidence of CAP and S. pneum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…More than half of the positive blood cultures in the present study were deemed to be contaminated (103/171, 60.6%), similar to reports by Min 3,25 With the wider access to pneumococcal conjugate vaccine in children aged <5 years 26 and Hib vaccine, 27 it is likely that in the present cohort the rate of positive blood cultures was also decreased in the 2015-2017 period, as well as the rate of positive S. pneumoniae and Hib isolations. With more vaccines available, the proportion of contaminated cultures may increase.…”
Section: Discussionsupporting
confidence: 88%
“…More than half of the positive blood cultures in the present study were deemed to be contaminated (103/171, 60.6%), similar to reports by Min 3,25 With the wider access to pneumococcal conjugate vaccine in children aged <5 years 26 and Hib vaccine, 27 it is likely that in the present cohort the rate of positive blood cultures was also decreased in the 2015-2017 period, as well as the rate of positive S. pneumoniae and Hib isolations. With more vaccines available, the proportion of contaminated cultures may increase.…”
Section: Discussionsupporting
confidence: 88%
“…As in previous studies (4,8,10,11), in the present study, the number of patients hospitalized for pneumonia in the secondary medical facility declined after the beginning of official financial support of PCV vaccination. In particular, the number of patients with pneumonia other than confirmed viral or mycoplasmal pneumonia was markedly reduced.…”
Section: Discussionsupporting
confidence: 81%
“…In Japan, the incidence of pneumococcal meningitis and bacteremia in children was markedly decreased after the introduction of PCV7 in 2010 (7). In addition, the reduction of community-acquired pneumonia and pneumococcal pneumonia in children aged < 5 years was also observed in Japan (8).…”
Section: Introductionmentioning
confidence: 95%
“…As previously described, the effectiveness of PCV7 against pneumonia ranges from 65% to 6.0% . In Chiba City, Japan, a population‐based study showed that the annual incidence rate ratio of CAP was 0.81, and the OR for pneumococcal pneumonia incidence was 0.60, when comparing post‐vaccine with pre‐vaccine periods . The effectiveness of PCV7 against invasive pneumococcal disease (IPD) has been shown by the rapid and large decrease in the number of IPD patients after its introduction into Japan and the USA .…”
Section: Discussionmentioning
confidence: 99%
“…found a PCV7‐associated reduction in pneumonia of 6.0%. In Japan, Naito et al . reported very recently that the annual incidence rate ratio of CAP was 0.81, when comparing the post‐vaccine with pre‐vaccine period.…”
mentioning
confidence: 99%